IDENTIFICATION OF HYPERTENSIVE PATIENTS WITH INCREASED BLOOD PRESSURE VARIABILITY USING DIFFERENT MEASUREMENT METHODS BEFORE AND AFTER TREATMENT: THE REVERENT TRIAL. (June 2022) - Kollias, Anastasios; Kyriakoulis, Konstantinos; Bilo, Grzegorz; Soranna, Davide; Liu, Chang-Yuan; Pengo, Martino; Zambon, Antonella; Zhang, Wei; Wang, Jiguang; Stergiou, George; Parati, Gianfranco
Abstract : Objective: Blood pressure (BP) variability (BPV) can be assessed with office (OBP), home (HBP), and ambulatory BP (ABP) measurements. In this analysis, BPV indices assessed using all the three methods were compared before and 10 weeks after administering antihypertensive drug treatment. Design and method: Untreated hypertensives (or treated after washout period) with elevated BPV (systolic HBP standard deviation [SD] > 7 mmHg and/or systolic daytime ABP SD > 12 mmHg), were nalysedd to ramipril 10 mg or nifedipine gastrointestinal therapeutic system (GITS) 30 mg once daily, in the context of a multicenter 10-week, prospective, nalysedd, open-label, blinded-end point study. BPV was assessed using SD and coefficient of variation (CV) [weighted SD (wSD) and weighted CV (wCV) for 24h-ABP variability) of individual measurements. Results: Data from 146 participants from three research centers (Athens, Milan, Shanghai) were nalysed (mean age 53 ± 10 [SD] years, males 60%, baseline systolic OBP, HBP and 24h-ABP 143 ± 10, 138 ± 10, and 143 ± 10 mmHg, respectively). All BPV indices (except for diastolic OBP) presented significant correlations in terms of pre- vs post- treatment, with ABP indices (especially diastolic) achieving the strongest correlations (Table). Moreover, out-of-office BPV indices (especially ABP) presented fair to moderate agreement in detecting participants with high BPV (top quartile of respective distribution) pre- vs post- treatment. Conclusions: Untreated hypertensives with high out-of-office BPV retain this classification even after BP lowering therapy, which suggests that BPV is an intrinsic feature of the individuals' BP.